Катастрофи у системах і відновлення після них - Федосєєнко, А. О. (ХНУРЕ, 2023)
A disaster, like any other event, is the result of self-organization of an open system. The development of such systems alternates between two stages - evolutionary and revolutionary. The goal of this work is to create some models for human-machine-environment systems, predicting catastrophic points for these systems and create some strategies for the passage of the disaster and disaster recovery.
Keywords: катастрофа; відновлення; оптимальна стратегія